Synthesis of (−)-6,7-dideoxysqualestatin H5 by carbonyl ylide cycloaddition–rearrangement and cross-electrophile coupling - Fegheh-Hassanpour, Y; Arif, T; Sintim, H; Al Mamari, H; Hodgson, D (American Chemical Society, 2017)
An asymmetric synthesis of (−)-6,7-dideoxysqualestatin H5 is reported. Key features of the synthesis include: (1) highly diastereoselective n-alkylation of a tartrate acetonide enolate and subsequent oxidation−hydrolysis to provide an asymmetric entry to a β-hydroxy-α-ketoester motif; (2) facilitation of Rh(II)-catalyzed cyclic carbonyl ylide formation−cycloaddition by cogeneration of keto and diazo functionality through ozonolysis of an unsaturated hydrazone; and (3) stereoretentive Ni-catalyzed Csp3−Csp2 cross-electrophile coupling between tricarboxylate core and unsaturated side-chain to complete the natural product.